Disentangling Pantomime From Early Sign in a New Sign Language: Window Into Language Evolution Research - Mineiro, Ana; Báez-Montero, Inmaculada Concepción; Moita, Mara; Galhano-Rodrigues, Isabel; Castro-Caldas, Alexandre (Frontiers in Psychology, 2021)
In this study, we aim to disentangle pantomime from early signs in a newly born sign language: Sao Tome and Principe Sign Language. Our results show that within two years of contact, a community of 100 participants interacting everyday was able to build a shared language. The growth of linguistic systematicity, across a two year time-frame, which includes a decrease of pantomime, reduction of the amplitude of signs and an increase in articulation economy, showcases a learning and social interaction process that constitutes a continuum and not a cut-off system. The human cognitive system is endowed with mechanisms for symbolization that allow the process of arbitrariness to unfold and the expansion of linguistic complexity. Our study helps to clarify the role of pantomime in a new sign language and how this role might be linked with language itself, showing implications for language evolution research.